Автоматизована система керування зарядкою квадрокоптера - Брюховецький, О. А. (ХНУРЕ, 2021)
The method of increasing the autonomy of quadcopters is analyzed in the work. The method of increasing productivity due to the Autonomous charging station is considered. The main problems and their solutions, advantages are considered.
Keywords: квадрокоптери; керування зарядкою квадрокоптера